EVOLUTION OF THE INSTITUTIONAL STRUCTURE OF THE KYRGYZ REPUBLIC: FROM A PARLIAMENTARY SYSTEM TO A PRESIDENTIAL GOVERNANCE MODEL (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This study analyzes contemporary public administration, focusing on the presidential and parliamentary systems. The choice of a particular system of government is determined by a combination of historical, cultural, and geopolitical factors. Particular attention is paid to the powers of the president and their impact on the functioning of the various branches of government. The advantages and disadvantages of both systems are also considered. In the context of Kyrgyzstan, the role of the country’s parliament is analyzed, as well as the duality of constitutional reforms, which impacts democratic institutions. One of the problems identified in the study is the low institutionalization of political parties, which hinders the development of democracy within these organizations. The role of the legislative branch and the main factors determining its effectiveness are also discussed. The objective prerequisites for a return to the presidential form of government are considered, and the main provisions of the 2021 constitutional reform are revealed. Within the analysis of amendments to the Constitution, special attention is paid to the functions of the president, the procedure for forming the government, and changes in the electoral system and the structure of parliament that were introduced as a result of this reform are analyzed. The need to consider the influence of informal institutions and develop mechanisms for balancing presidential power and the multiparty system to ensure the stability of the governance system is emphasized.
Keywords: constitutional reforms, governance system, parliamentary republic, presidential form of government, electoral system, informal institutions, political system